Effectiveness of group guidance using Expressive Arts Therapy in improving self management of sexual harassment among vocational high school students in city of Pinang - Rismaniar Rismaniar; Firman Firman (International Journal of Applied Counseling and Social Sciences, 2021)
The case of sexual harassment are more and more extends, spread, and found a lot in several areas, the city, even among all these villages not only the community but also in the world of education in indonesia. Sexual harassment case it is becoming even diverse and no longer eat his victims who are in the age range of adult , but those who are in the age range of teenagers even children very much a victim or an offender sexual harassment. Sexual harassment that occured in schools happened because of incompetence students in regulating and manage himself with good. One of the efforts was to enhance the capacity of students in regulating and manage himself in do sexual harassment is to hold guidance services use the art of expressive of group. The sample as many as 13 students for the experiments on class, X, XI  and 13, students to the control group the sample used are proportionate stratified random sampling. Statistical analysis of data used in this research are nonparametrik statistics. Instruments gather data using the model scale likert, data analyzed using wilcoxon signed ranks kolmogorov-smirnov test and with the help of two independent sampels spss 20. Version. The findings of this study are: 1) there is a significant differences self management group experiment before and after given guidance services group use an expressive art therapy, 2) there is a significant differences self management control group before and after the guidance given services without special treatment, 3) there is a differences self management group experiment given guidance services group use an expressive art therapy to the control group given guidance services group about self management without special treatment , this was apparent from the score average postest group experiment rise higher than the average posttest score control group.